Community Translation Research and Practice - GONZALEZ, Erika; Stachowiak-Szymczak, Katarzyna; Amanatidou, Despina (Taylor & Francis, 2023)
Community translation or public service translation is on a global scale often unregulated and dependent on individual awareness, good will and even charity work. The social impact and mission of community translation, the key role of the translator's psycho-sociocultural awareness and its role depending on local and global changes in human migration and linguistic diversity make community translation a constantly evolving and yet under-investigated activity and profession. This book covers key practical and theoretical approaches towards community translation, providing insights into the current state of the field and the latest research, trends, guidelines, initiatives and gaps. Combining knowledge in the areas of translator ethics, pedagogy, legal, and social and health-related settings, this volume covers community translation in a wide range of countries and regions. Community Translation: Research and Practice is an essential guide both for those studying and working in this area worldwide. This volume is a springboard for further studies and research in this emerging field.